Mendorong Reformasi Sistem Manajemen Keselamatan dan Kesehatan Kerja untuk Pekerjaan Konstruksi di Indonesia Melalui Pembelajaran dari Occupational Safety and Health Administration di Amerika Serikat - Cahya, Fanny Dwi; Rahma, Siti; Simbolon, Cika; Arifin, Daud (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2025)
Occupational safety and health are crucial elements in the implementation of construction projects, considering the high risk of work accidents in this sector. This study aimed to analyze the differences in occupational safety and health management systems between Indonesia and the United States; in order to identify best practices that can be adopted to improve the effectiveness of the construction safety management system in Indonesia. This study was conducted using a literature study method; which examines regulations, implementation, safety culture, and occupational safety technology from various official sources and scientific publications. The results of the study showed that the United States, through the occupational safety and health administration, has a more structured occupational safety and health system, with comprehensive worker training, strict supervision, and adoption of high technology. In contrast, in Indonesia, the implementation of the occupational safety and health management system still faces challenges in the form of low compliance, minimal training, and weak law enforcement. The conclusion of this study emphasizes the need for reform of the occupational safety and health management system in Indonesia by increasing the capacity of supervisors, adopting technology, and building a safety culture, with reference to best practices from the United States.Keywords: construction work; Indonesia; United States; occupational safety and health; occupational safety and health management system; occupational safety and health administration ABSTRAK Keselamatan dan kesehatan kerja merupakan elemen krusial dalam pelaksanaan proyek konstruksi, mengingat tingginya risiko kecelakaan kerja pada sektor ini. Studi ini bertujuan untuk menganalisis perbedaan sistem manajemen keselamatan dan kesehatan kerja antara Indonesia dan Amerika Serikat; guna mengidentifikasi praktik terbaik yang dapat diadopsi untuk meningkatkan efektivitas sistem manajemen keselamatan konstruksi di Indonesia. Studi ini dilakukan menggunakan metode studi literatur; yang mengkaji regulasi, implementasi, budaya keselamatan, serta teknologi keselamatan kerja dari berbagai sumber resmi dan publikasi ilmiah. Hasil studi menunjukkan bahwa Amerika Serikat, melalui occupational safety and health administration, memiliki sistem keselamatan dan kesehatan kerja yang lebih terstruktur, dengan pelatihan pekerja yang menyeluruh, pengawasan ketat, dan adopsi teknologi tinggi. Sebaliknya, di Indonesia, implementasi sistem manajemen keselamatan dan kesehatan kerja masih menghadapi tantangan berupa rendahnya kepatuhan, minimnya pelatihan, serta lemahnya penegakan hukum. Kesimpulan dari studi ini menegaskan perlunya reformasi sistem manajemen keselamatan dan kesehatan kerja di Indonesia melalui peningkatan kapasitas pengawas, adopsi teknologi, dan pembangunan budaya keselamatan, dengan mengacu pada praktik terbaik dari Amerika Serikat.Kata kunci: pekerjaan konstruksi; Indonesia; Amerika Serikat; keselamatan dan kesehatan kerja; sistem manajemen keselamatan dan kesehatan kerja; occupational safety and health administration